Multilingualism in Nigeria: A socio-linguistic investigation of Ewan Alufohai’s The Moto-Boy - Okugbe, Monday A.; Ambrose, Lynda (Teaching English as a Foreign Language Journal, 2024)
This study is a socio-linguistic examination of Ewan Alufohai’s The Moto-Boy. The text is a Nigerian novel, pre-occupied with the challenges facing road transportation and those involved in the business. This paper, therefore, attempts to explore the interplay of the linguistic variables of function, use and usage of contextualization and Nigerianization of Nigerian English (NE) in the text, by exemplifying these with some empirical data, drawn from the text. Adopting the sociolinguistic theoretical model, derived from the systemic functional (SF) approach, the selected data in the text are subjected to analytical investigation, to show that Nigeria is a multilingual society. The study reveals that language variations employed in the text, are reflections of the uniqueness and peculiarities of the diverse cultures inherent in Nigeria, with a view to underlying the indispensability of multiple language situation in a multilingual society. The analysis of the features of language variations in the text selected, is aimed at enhancing communication in Nigeria’s diverse cultural setting. Therefore, the findings in the study shows that the use of creative language variations in the text enhances readers’ deep understanding of their meanings in the context of use.